Relating american football age of first exposure to patient-reported outcomes and medical diagnoses among former national football league players: an NFL-LONG study - Lempke, L. B.; Walton, S. R.; Brett, B. L.; Chandran, A.; DeFreese, J. D.; Mannix, R.; Echemendia, R. J.; McCrea, M. A.; Guskiewicz, K. M.; Meehan III, W. P.; Kerr, Z. Y. (Sports Medicine, 2023)
Background: The age of first exposure (AFE) to American football participation is a growing concern for late-life function. Mixed evidence exists surrounding AFE and may be attributed to varied methods employed across studies. Objective: To examine the associations between AFE to American football participation with measures of cognitive, behavioral, and physical function and brain-related medical diagnoses across age categories among former National Football League players. Methods: We conducted a cross-sectional survey of 1784 former players (age: 52.3 ± 16.3 years, AFE: 11.3 ± 2.9 years, years of football: 17.5 ± 4.5 years, 86.9% = one lifetime concussion). Players completed a general health questionnaire recording demographics, football playing history (including AFE), and diagnoses (anxiety, depression, any form of dementia, mild cognitive impairment). Players completed Patient-Reported Outcomes Measurement Information System (PROMIS) measures assessing domains of cognitive and physical function, anxiety, depression, sleep disturbance, pain interference, and emotional-behavioral dyscontrol. Multivariable linear and binomial regression models were used to examine the associations of AFE and age with PROMIS outcomes and diagnoses, respectively. Results: No significant AFE by age interactions were detected for PROMIS outcomes (p = 0.066) or diagnoses (p = 0.147). Younger AFE associated with higher PROMIS scores of anxiety (B = - 0.22, p = 0.016), depression (B = - 0.22, p = 0.010), sleep disturbances (B = - 0.16, p = 0.007), pain interference (B = - 0.19, p = 0.014), and emotional-behavioral dyscontrol (B = - 0.22, p = 0.019). Age was associated with all PROMIS outcomes (p = 0.042). AFE was not associated with the prevalence of anxiety, depression, dementia, or mild cognitive impairment (p = 0.449), while age was (p = 0.013). Conclusions: AFE was significantly associated with PROMIS outcomes, albeit low-strength associations (i.e., effect sizes), but not with diagnoses. Our findings indicate AFE is a significant but minor contributing factor for health-related quality of life in this cohort. Future work should incorporate additional characterizations of cumulative head impacts and related factors when examining long-term outcomes associated with football participation.